Adverse reactions related to proton pump inhibitors in pediatric population: an analysis of spontaneous reporting data. Issue 1 (2nd January 2022) - Dipasquale, Valeria; Cicala, Giuseppe; Laganà, Francesca; Cutroneo, Paola; Felicetti, Patrizia; Potenza, Simona; Trimarchi, Giuseppe; Spina, Edoardo; Romano, Claudio
ABSTRACT: Background: The use of proton pump inhibitors (PPIs) has increased in the last 10 years in children. Data regarding their safety profile are limited. The aim of this study was to analyze data from the Italian spontaneous reporting system (SRS) database to evaluate the incidence and characteristics of PPI-related adverse drug reactions (ADRs) in children. Research design and methods: This was an observational, retrospective study analyzing PPI-related ADR reports in children in the Italian SRS database between January 1 st, 2001, and December 31 st, 2020. ADRs were coded according to the system organ class term level. Factors associated with ADR seriousness were investigated. Results: Seventy spontaneous reports of ADRs related to PPIs were analyzed. Esomeprazole and lansoprazole caused the highest number of ADRs equally (27% respectively), and the most frequently reported ADRs presented with gastrointestinal (24%) and/or skin manifestations (21.3%). More than a half of PPI prescriptions were off label for pediatric population. Serious ADRs were 19 (27.1%). Serious ADRs were more frequent in reports presenting PPIs combined with other drugs in comparison to reports with PPI single therapies (p = 0.03). Conclusions: PPI-related ADRs in children are mostly not serious, and combination therapy seems to be associated with ADR seriousness.